50 years of growth at CIAT: Moments and milestones - International Center for Tropical Agriculture (2023)
This expanded version of our timeline is a copy in pdf of the large-format timeline we installed on our Palmira campus in 2017 during CIAT's 50th anniversary. It displays photos, short texts, and cartoons, documenting CIAT's most significant moments and milestones in its first 50 years.